Nominal phrases from a Scandinavian perspective - Julien, Marit (Linguistik aktuell ;, 2005)
This monograph presents a new model of the internal syntax of nominal phrases. The model is mainly based on Scandinavian, since with the wide range of variation that Scandinavian displays in the nominal domain, despite the close genetic relationship between the different varieties, Scandinavian is particularly well-suited for explorations into nominal syntax. Among the topics covered are the basic syntactic structure of nominal phrases, definiteness, adjective phrases, possessors, relative clauses, and nominal predicates. The model is however meant to be a tool for analysing the nominal phrase.